2017
DOI: 10.1080/23120053.2017.1335962
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal sepsis in a Nigerian Tertiary Hospital: Clinical features, clinical outcome, aetiology and antibiotic susceptibility pattern

Abstract: Background: Neonatal sepsis is a significant cause of neonatal mortality in developing countries. The aetiological agents and their antimicrobial susceptibility patterns are dynamic. Objectives: This study determined clinical features, aetiology, antimicrobial susceptibility and clinical outcome of neonatal sepsis in a Nigerian Tertiary Hospital. Methods: Neonates undergoing sepsis evaluation at a Nigerian Tertiary Hospital were included in the study. Demographic and clinical information were obtained using st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…Additionally, most neonates with culture proven bacteremia were born at a health institution where most neonatal sepsis is arising from hospital acquired infections. Resistance rates of isolated Gram-positive bacteria against third generation Cephalosporines were also high in our study which is consistent with studies from Nigeria, Tanzania, Georgia, Iran and other developing countries [11, 12, 15, 17, 1923].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, most neonates with culture proven bacteremia were born at a health institution where most neonatal sepsis is arising from hospital acquired infections. Resistance rates of isolated Gram-positive bacteria against third generation Cephalosporines were also high in our study which is consistent with studies from Nigeria, Tanzania, Georgia, Iran and other developing countries [11, 12, 15, 17, 1923].…”
Section: Discussionsupporting
confidence: 92%
“…Guidelines on neonatal sepsis management in most centers [7, 19] recommend Ampicillin and Gentamycin as first-line empiric therapy. Unfortunately, most identified bacteria were highly resistant in this current report.…”
Section: Discussionmentioning
confidence: 99%
“…These deaths result mainly from infections, prematurity and perinatal asphyxia [5], while neonatal sepsis alone accounts for about 1.4 million of neonatal deaths annually and about 75% of these deaths occur in the first week of life [6]. Recent studies in developing countries show varying incidence of neonatal sepsis, aetiological agents and antimicrobial sensitivity pattern [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…2–4 The predominant pathogens are usually Gram-negative bacteria in developing regions, while in developed regions, they are group B Streptococcus (GBS) and Escherichia coli . 5–7 Recently, studies have suggested changes in the spectrum of EOS pathogens and bacterial resistance patterns, which are important factors that require adjustments in EOS management. 2,8…”
mentioning
confidence: 99%